Search for supersymmetry in pp collisions at √s=13 TeV with 137 fb−1 in final states with a single lepton using the sum of masses of large-radius jets; Physical Review D; Vol. 101, iss. 5 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Tyurin N. E. Nikolay Evgenjevich; Babaev A. A. Anton Anatoljevich (2020, 2020)
Title screen